(untitled) (Scientia Agropecuaria, 2026)
Parasitic nematodes in crops are a serious threat in worldwide agricultural production. The concerns regarding the environmental and toxicological risks associated with the usage of chemical substances encourage the pursuit of more environmentally friendly alternatives to control phytopathogenic nematodes. It’s been considered viable to employ biological control agents, like bacteria, which besides having mechanisms that can control nematodes are also growth promoters for plants. This review’s goal is to broaden the comprehension over bacterial agent mechanisms to suppress nematodes population and its phosphorus solubilization capability. Bacteria have antagonist interactions capable of producing metabolites, increasing the systemic resistance to plants and space competition. Chemical compounds produced by bacteria can mineralize organic phosphorus from the soil and supply it for plant adsorption. Rhizospheric bacteria have synergic action to improve growth and plant protection. This review’s approach aims to contribute to the understanding of rhizobacterial potential, which dual action in vegetative growth and as nematophagus agents, makes them key tools for a sustainable management of phytopathogenic nematodes. This perspective opens the possibility to include these microorganisms and their metabolites in innovative plans for agricultural management, which can respond to productivity demand and climate change challenges.